Color and illuminance level of lighting can modulate willingness to eat bell peppers. (7th January 2014) - Hasenbeck, Aimee; Cho, Sungeun; Meullenet, Jean‐François; Tokar, Tonya; Yang, Famous; Huddleston, Elizabeth A; Seo, Han‐Seok
Abstract BACKGROUND Food products are often encountered under colored lighting, particularly in restaurants and retail stores. However, relatively little attention has been paid to whether the color of ambient lighting can affect consumers' motivation for consumption. This study aimed to determine whether color (Experiment 1) and illuminance level (Experiment 2) of lighting can influence consumers' liking of appearance and their willingness to eat bell peppers. RESULTS For red, green, and yellow bell peppers, yellow and blue lighting conditions consistently increased participants' liking of appearance the most and the least, respectively. Participants' willingness to consume bell peppers increased the most under yellow lighting and the least under blue lighting. In addition, a dark condition (i.e. low level of lighting illuminance) decreased liking of appearance and willingness to eat the bell peppers compared to a bright condition (i.e. high level of lighting illuminance). CONCLUSION Our findings demonstrate that lighting color and illuminance level can influence consumers' hedonic impression and likelihood to consume bell peppers. Furthermore, the influences of color and illuminance level of lighting appear to be dependent on the surface color of bell peppers. © 2013 Society of Chemical Industry